Belajar Desain Denagn Mudah Menggunakan Aplikasi Canva (Di SMK Grafika Lebak Bulus) - Imam Hidayat; Enjah Pipit Fitriyadi; Fordiana Ekawati (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The purpose of this activity is to introduce and provide training and mentoring to students at SMK Grafika Yayasan Lektur Lebak Bulus in making designs easily using the Canva application, learning using the Canva application as material to improve competence and hard skills in the world of digital-based education. The expected benefits of this activity are that students know about design learning, competence, and hard skills in making designs using the Canva application making various image and video designs, learning that contains from introduction, and installation to practice making designs. The methods used are lectures, discussions, and mentoring methods. The activity was located at SMK Grafika Yayasan Lektur Lebak Bulus with 24 students. The results of the activities that all students have carried out can help, them understand, install, and use the Canva application to make good designs.